SOCIO-DEMOGRAPHIC STUDY OF HEPATITIS C PATIENTS VISITING TERTIARY CARE HOSPITAL - Mukhtar, Osama; Zaheer, Fozia; Malik, Muhammad Farooq; Khan, Junaid Sarfraz; Ijaz, Tayyaba (Journal of Ayub Medical College Abbottabad, 2015)
Background: Hepatitis C is a very common blood-borne disease of liver caused by Hepatitis C Virus and about two third of these patients will ultimately end up having liver cirrhosis or hepatocellular carcinoma. This study was carried out to determine the sociodemographic status of the hepatitis C infected patients visiting tertiary care hospitals in Lahore, Pakistan. Methods: This study was conducted during the months of October and November 2009. In this cross sectional study, 154 volunteer patients of HCV were included. They were investigatedfor sociodemographic variables and were statistically analysed by SPSS-15. Results: Of these 154 patients, a high percentage of patients were females (70.1%). Majority of the patients belonged to the families of labour occupation (39.4%) of which 71.4 % were illiterate. Gender was found significantly associated with categories of sleep disturbance (p<0.05) and tension (p<0.05) among HCV patients. Married patients were significantly associated with tension (p<0.05) and a significant emotional and behavioural change in their attitude was also found (p<0.05). Patients with shorter interval after first diagnosis of the disease felt more emotional and had greater behavioural changes in their attitude (p<0.05). Conclusion: Incidence of Hepatitis C was higher in females and married females with shorter interval after first diagnosis of the disease were more depressed.